Comparison of the cardiothoracic ratio between postmortem and antemortem computed tomography. (January 2017) - Okuma, Hidemi; Gonoi, Wataru; Ishida, Masanori; Shirota, Go; Kanno, Shigeaki; Shintani, Yukako; Abe, Hiroyuki; Fukayama, Masashi; Ohtomo, Kuni
Highlights: The postmortem changes in cardiothoracic ratio (CTR) were assessed by CT. The postmortem CTR was greater than antemortem CTR regardless of the heart condition. No confounding factors showed significant associations with postmortem CTR changes. The CTR threshold of 0.54 identified cardiomegaly with the greatest accuracy. Abstract: As postmortem imaging has gained prominence as a supplement to traditional autopsy, it is important to understand the normal postmortem changes to enable the accurate evaluation of postmortem imaging. No studies have evaluated the postmortem changes in cardiothoracic ratio (CTR) compared with antemortem images in the same subjects. We studied 147 consecutive subjects who underwent antemortem and postmortem CT, and autopsy. Postmortem CT was performed <23 h after death and was followed by autopsy. The subjects were divided into three groups: normal heart, old myocardial infarction, and CPR-treated hearts. CTR was compared between antemortem and postmortem CT using paired t tests, which revealed that the CTR was greater on postmortem CT than on antemortem CT in all groups (mean CTR: 0.53 ± 0.06 vs. 0.50 ± 0.06, respectively; P < 0.01). Sex, age, time elapsed since death, and the causes of death were examined as potential confounding factors for the postmortem changes in CTR, but no significant associations were found. Receiver-operating characteristic (ROC) curves were used to determine CTR values for cardiomegaly, which was defined according to the autopsy weight of the heart. The area under the ROC curve was 0.71 (95% confidence interval 0.63–0.79). The CTR threshold of 0.54 identified cardiomegaly with the greatest accuracy, compared with the general threshold of 0.50. In conclusion, the CT-determined CTR increases after death, irrespective of the heart's condition. We should be cautious of overdiagnosis of cardiomegaly on postmortem CT, and new criteria for interpreting cardiomegaly on postmortem CTR are needed.